Leadership Training to Increase Need Satisfaction at Work: A Quasi-Experimental Mixed Method Study - Tafvelin, Susanne; von Thiele Schwarz, Ulrica; Stenling, Andreas (Frontiers in Psychology, 2019)
With a growing number of studies showing the applicability of the self-determination theory for various work and organizational outcomes, the next logical step is to investigate if and how employee need satisfaction at work can be purposefully increased through an intervention. The purpose of the present study was to test whether we could train managers’ display of autonomy, competence, and relatedness support towards employees and whether this resulted in improved employee need satisfaction, well-being, and job performance. Data were obtained from 37 managers (rated by N = 538 subordinates) assigned to either an experimental or control condition at four time points: before, during, and after the training. We also used focus group interviews to evaluate the experience of the training. The quantitative analyses showed no statistically significant improvement in managers’ display of needs support or employee need satisfaction. However, the qualitative data pointed towards important factors related to the implementation of need supportive leadership training that should be considered.